Proceedings of the 4th International Conference on Electrical Engineering and Control Applications ICEECA 2019, 17–19 December 2019, Constantine, Algeria - Bououden, Sofiane; Chadli, Mohammed; Ziani, Salim; Zelinka, Ivan (Lecture Notes in Electrical Engineering, 2021)
XIX, 1288 p. 754 illus., 600 illus. in color.